2003
DOI: 10.1016/s0022-3115(02)01470-8
|View full text |Cite
|
Sign up to set email alerts
|

Interpretive modeling of simple-as-possible-plasma discharges on DIII-D using the OEDGE code

Abstract: Recently a number of major, unanticipated effects have been reported in tokamak edge research raising the question of whether we understand the controlling physics of the edge. This report is on the first part -here focused on the outer divertor -of a systematic study of the simplest possible edge plasma -no ELMs, no detachment, etc. -for a set of 10 repeat, highly diagnosed, single-null, divertor discharges in DIII-D. For almost the entire, extensive data set so far evaluated, the matches of experiment and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 8 publications
2
51
0
Order By: Relevance
“…Taking into account the radial profile of the C-ions in the main plasma, from CER, the particle confinement time is found to be τ c ~ 5.5 msec (where τ c ≡ (total core content)/(methane puff rate)). This value is fairly close to the values reported by West [13], of ~ 10 ms, also for CH 4 puffing into DIII-D, although using localized wall puffing. The closely related OEDGE modeling of Elder [7] showed that τ c would be ~4X higher if the CH 4 were ionized at the separatrix, rather than at the actual location -~ 3 cm radially outside the separatrix.…”
Section: Experiments and Modelingsupporting
confidence: 90%
See 2 more Smart Citations
“…Taking into account the radial profile of the C-ions in the main plasma, from CER, the particle confinement time is found to be τ c ~ 5.5 msec (where τ c ≡ (total core content)/(methane puff rate)). This value is fairly close to the values reported by West [13], of ~ 10 ms, also for CH 4 puffing into DIII-D, although using localized wall puffing. The closely related OEDGE modeling of Elder [7] showed that τ c would be ~4X higher if the CH 4 were ionized at the separatrix, rather than at the actual location -~ 3 cm radially outside the separatrix.…”
Section: Experiments and Modelingsupporting
confidence: 90%
“…This injection is unusual in being toroidally-symmetrical -CH 4 injection was through the upper outer pumping plenum ( Fig. 1) -thus justifying the standard, but often not satisfied, code assumption of symmetry.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…A low-density L-mode plasma was chosen as the target plasma in the 2003 13 C injection experiment [Stangeby_JNM03]: n e = 2.8 "10 19 m -3 , or n e n GW~0 .28, where n GW is the Greenwald density [Greenwald_NF88]. Plasma heating was predominately ohmic heating with short neutral beam pulses applied to permit charge exchange spectroscopy measurements.…”
Section: A 13 Ch 4 Injection Into L-mode Plasmasmentioning
confidence: 99%
“…To clarify the controlling physics processes of carbon transport in DIII-D, comprehensive modeling using the OEDGE [Stangeby_JNM03] and UEDGE [Rognlien_JNM92] code packages has been carried out. In general, carbon migration involves (1) primary erosion due to plasma impact on plasma-facing components, (2) transport, dissociation, and ionization of hydrocarbon molecules and carbon atoms, (3) initial deposition, and (4) multi-step re-erosion and redeposition [Matthews_JNM05].…”
Section: Introductionmentioning
confidence: 99%